Hardness and flexural properties of heat treated SKD61 medium carbon steel - Hafizuddin, Mohamad Shafiee (2016)
Nowadays, medium carbon steel is widely used in engineering industry because of their balance properties. To change the mechanical properties of medium carbon steel, it needs to undergo heat treatment process. Heat treatment process is a combination of controlled heating and cooling a metal or alloy to achieve desired physical and mechanical properties. In order to modify the microstructure and desired mechanical properties, there are commonly heat treatments that often been used (annealing, normalizing, hardening and tempering). For this study, the samples are divided into two parts which are untreated and heat treated. For heat treated, the specimens were heating at 900 oC with soaking time 90 minutes and the cooled in different cooling medium which are quenched in water, inside the furnace and air. Then, the hardened specimens were tempered at two different temperatures. Rockwell Hardness test and flexural test are performed to investigate the hardness and flexural properties of the specimens and fractured surface of the specimens is observe using Field Emission Scanning Electron Microscope (FESEM). The result found that the hardness and flexural properties of the specimen is higher when the specimen is quenched in water compare with others cooling medium. Besides that, the hardened steel shows brittle fractured surface which consist of transgranular cleavage. Fractured surface for untreated, annealed and tempered 500⁰C specimen shows ductile failure mode with more plasticity deformation occurred.